Post-harvest losses in fruits and vegetables: The Kenyan context - Ridolfi, Carlotta; Hoffmann, Vivian; Baral, Siddhartha (International Food Policy Research Institute, 2018)
This report collates and contextualizes available evidence on post-harvest losses (PHL) in horticultural crops in Kenya. We begin by outlining the extent of PHL in horticultural crops and its repercussions in the context of food security and poverty reduction. We then describe the growing importance of the horticulture sector in Kenya and its growth potential, especially in terms of exports. Following this discussion, we detail PHL for two important horticultural crops, mangoes and tomatoes, for which Kenya-specific evidence is available. We discuss ways to mitigate PHL from three angles: technological, economic or behavioral, and institutional. Documenting cost-effective technological interventions to mitigate PHL, we catalogue ways to tackle PHL at the individual farmer level. We then highlight behavioral bottlenecks to adoption of such technologies and the need to design interventions in ways that address these. Finally, we discuss structural and institutional changes that would need to accompany individual-level interventions to bring about significant reductions in PHL.